LATENT STRUCTURE OF MOTOR AND FUNCTIONAL VARIABLES ON A SAMPLE OF JUNIOR FOOTBALL PLAYERS (Fiep Bulletin - online, 2014)
Football is a complex sport. Success in football depends on a deep understanding of football players’ developmental phases, as well as of the effects of particular motor and functional abilities. This is particularly true for the junior category of football players (age 17- 19). The purpose of this research was to determine the latent structure of motor and functional characteristics of junior football players. The sample of subjects comprised 100 football players, juniors of the Croatian First Football League. The variables used for the assessment of motor and functional abilities included 22 tests (6 agility tests, 3 functional ability tests, 1 shot-type explosive power test, 4 sprint tests and 8 isokinetic force tests). A component model of factor analysis was used to determine the latent structure of motor and functional variables. Four latent variables were revealed: primary agility as the first factor, followed by endurance, explosive power and isokinetic force.
Keywords: football; junior players; motor abilities; functional abilities